Epidermal stem cells (ESCs) accelerate diabetic wound healing via the Notch signalling pathway. Issue 4 (5th August 2016) - Yang, Rong-Hua; Qi, Shao-Hai; Shu, Bin; Ruan, Shu-Bin; Lin, Ze-Peng; Lin, Yan; Shen, Rui; Zhang, Feng-Gang; Chen, Xiao-Dong; Xie, Ju-Lin
Abstract : Epidermal stem cells (ESCs) accelerate diabetic wound healing via the Notch signalling pathway. Abstract : Chronic, non-healing wounds are a major complication of diabetes. Recently, various cell therapies have been reported for promotion of diabetic wound healing. Epidermal stem cells (ESCs) are considered a powerful tool for tissue therapy. However, the effect and the mechanism of the therapeutic properties of ESCs in the diabetic wound healing are unclear. Herein, to determine the ability of ESCs to diabetic wound healing, a dorsal skin defect in a streptozotocin (STZ)-induced diabetes mellitus (DM) mouse model was used. ESCs were isolated from mouse skin. We found that both the mRNA and protein levels of a Notch ligand Jagged1 (Jag1), Notch1 and Notch target gene Hairy Enhancer of Split-1 (Hes1) were significantly increased at the wound margins. In addition, we observed that Jag1 was high expressed in ESCs. Overexpression of Jag1 promotes ESCs migration, whereas knockdown Jag1 resulted in a significant reduction in ESCs migration in vitro . Importantly, Jag1 overexpression improves diabetic wound healing in vivo . These results provide evidence that ESCs accelerate diabetic wound healing via the Notch signalling pathway, and provide a promising potential for activation of the Notch pathway for the treatment of diabetic wound.